A Model of Digital Vo-Book with Crossword for Teaching and Learning Vocabulary in Seventh Grade Junior High School t Blitar: Research and Development - Julia Ike Darmayanti; Dian Fadhilawati; Adin Fauzi (JOSAR (Journal of Students Academic Research), 2022)
This research objectives are to develop a model of Digital Vo-Book with Crossword for Teaching and Learning Vocabulary, to find out the appropriateness of Digital Vo-Book with Crossword for Teaching and Learning Vocabulary, and to know the teachers' and students' perceptions toward the use of development Digital Vo-Book with Crossword for Teaching and Learning Vocabulary in Seventh Grade Junior High School. This research adapted Sugiyono's R & D model. These research problems consisted of six steps: (1) data collections and finding potential and problem, (2) design and development, (3) expert validation and revision, (4) teachers’ and students’ perceptions, (5) evaluation by experts and revision, and (6) final product and publication. The result of material validation 90.6% and media validation 85.7% included in the "Very Valid" category. The result of the teacher's perception of 88.2% and the student’s perception 86.98% included in the "Very Good" category. It means that Vo-Book can be applied as an alternative media for teaching and learning vocabulary to seventh-grade students in Junior High School. The final product of the model consisted of a digital Vo-Book with a crossword, and 3 guidebooks for student, teacher, and public.